If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 37 = 9 + -4h Solving 37 = 9 + -4h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '4h' to each side of the equation. 37 + 4h = 9 + -4h + 4h Combine like terms: -4h + 4h = 0 37 + 4h = 9 + 0 37 + 4h = 9 Add '-37' to each side of the equation. 37 + -37 + 4h = 9 + -37 Combine like terms: 37 + -37 = 0 0 + 4h = 9 + -37 4h = 9 + -37 Combine like terms: 9 + -37 = -28 4h = -28 Divide each side by '4'. h = -7 Simplifying h = -7
| -21+70m=77 | | 24x^2+18x-81=0 | | 68=-v+261 | | 2.3x+3.1y=10.8 | | 6(x-7)=3(2x-5) | | 25x^2-65x-30=0 | | x+17=52 | | x^2-15x-450=0 | | 18c-17=7 | | 3x+2-13x-3=55 | | 11d+d= | | 6(3*8)= | | -22+-3d=-88 | | 191=-v+98 | | 3x+2+13x-3=55 | | xy+5y-8x-40=0 | | x^2+55x-1500=0 | | 19x+4=365 | | 4y=8-2x | | 9h(h)+4h-44=0 | | 5184/-8= | | q+14=8(q+u) | | 3+-6x=y | | 4x+19=365 | | 2x-1-1=2 | | x^2-35x-450=0 | | -8.1+r=-7.3 | | 100y(y)-121=0 | | -0.78=1.18x | | 72*72= | | 19t(t)-36t-4=0 | | 0.33=n+1.33 |